Analisis Kebijakan Persediaan Just in Time di UMKM Mom's Yogurt - Novita Ria Simanjuntak; Roland Y.H. Silitonga (Jurnal Serambi Engineering, 2024)
The production process is important to the success of a business, and inventory is a key factor in maintaining smooth production. Problems often arise with the inventory of raw materials in the production process,especially when long storage can affect their quality, or when ordering is too frequent, resulting in high inventory costs. Mom's Yogurt, a manufacturer of preservative-free products, uses milk and sugar as its main ingredients. The purpose of this study is to find the optimal amount of raw materials to order, the optimal frequency of ordering, and to reduce inventory costs by using EOQ and JIT methods. Based on the research results, the optimal order quantities of milk and sugar according to EOQ are 548 litres and 100 litres, with order frequency of 6 and 3 times per year, respectively. The total inventory costs are Rp 139,643.08 and Rp 81,649.73, respectively. Using the JIT method, the optimal order quantities of milk and sugar are 3,750 litres and 235 litres, with an order frequency of 1 and 2 times per year, respectively, with total inventory costs of Rp 20,396.60 and Rp 33,994.40. Looking at the results of the calculation of total inventory cost, the results of the calculations with EOQ and JIT resulted in a significant reduction in the cost of milk and sugar inventory compared to the company's policy method. EOQ decreased by 89.29% and 83.78% respectively, while JIT decreased by 98.44% and 93.25% respectively.